2014
DOI: 10.14512/gaia.23.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Climate Change Adaptation. State of the Art and Lessons Learned from Ten OECD Countries

Abstract: Over the last years, communicating climate change adaptation has gained increasing attention in science and practise. This paper provides an overview of existing adaptation communication formats in ten OECD countries and offers recommendations for their successful design. Via online search we identified 278 communication formats on climate change adaptation. Based on a literature review and a consultation process with climate and communication experts from science and practise, a list of 16 success factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Effective adaptation communication is a process of engagement, requiring collaboration, understanding, and patience to achieve the desired outcome. The success factors for communicating adaptation consist of (1) trusted senders and opinion leaders inside the community; (2) content and messages should be explained and visualized in understandable ways, and the local people should become more familiar with clear implications for actions at different times, as well as adaptation languages, and positive terms, explained through concrete actions, should be related to responsible and high-priority planning, decision-making, and management of uncertainty; (3) messages and media should be framed, designed, and employed based on audiences or target groups: framing issues using communication formats and channels that are appropriate for the target group; and (4) receivers should be convinced regarding adaptation strategies [48][49][50][51].…”
Section: Factors Influencing Fishers' Decisions To Adapt and Expectatmentioning
confidence: 99%
“…Effective adaptation communication is a process of engagement, requiring collaboration, understanding, and patience to achieve the desired outcome. The success factors for communicating adaptation consist of (1) trusted senders and opinion leaders inside the community; (2) content and messages should be explained and visualized in understandable ways, and the local people should become more familiar with clear implications for actions at different times, as well as adaptation languages, and positive terms, explained through concrete actions, should be related to responsible and high-priority planning, decision-making, and management of uncertainty; (3) messages and media should be framed, designed, and employed based on audiences or target groups: framing issues using communication formats and channels that are appropriate for the target group; and (4) receivers should be convinced regarding adaptation strategies [48][49][50][51].…”
Section: Factors Influencing Fishers' Decisions To Adapt and Expectatmentioning
confidence: 99%
“…Communicating research findings in ways that change policy makers’ thinking and catalyze action on climate change is a dynamic, contextual, and highly politicized endeavor. Not surprisingly, climate change communication has emerged as an important area of research in recent years, and its evolution as a field of study has been well documented in this journal and others . Overall, we see trends in the literature towards a better understanding of the role of language (metaphors, words, strategies, frames, and narratives) in conveying climate change issues to stakeholders; and the power of norms, habits, and emotions in mediating the link between information provision and action …”
Section: Communicating For Changementioning
confidence: 84%
“…of protective behavior, including self-protective and altruistic behavior, and has systematized these determinants in theories such as Protection Motivation Theory (PMT; Rogers, 1983;Rogers & Prentice-Dunn, 1997), Health Belief Model (HBM; Champion & Skinner, 2008;Hochbaum, 1958), and Norm-Activation Theory (NAT; Schwartz, 1977). Furthermore, psychological intervention research has identified a number of effective interventions to change people's risk awareness and behavior (e.g., Mosler & Gutscher, 1998 (Wirth, Prutsch, & Grothmann, 2014). "Although there are many guidelines for climate communication, there is little empirical evidence of their efficacy" (Pidgeon & Fischhoff, 2011, p. 35).…”
Section: Research-article2017mentioning
confidence: 99%